2019
DOI: 10.33972/jhs.166
|View full text |Cite
|
Sign up to set email alerts
|

The Perpetuation of Online Hate: A Criminological Analysis of Factors Associated with Participating in an Online Attack

Abstract: Online extremism, or the use of information technology to profess attitudes devaluing others based on a characteristic such as race, religion, gender, or sexuality, is a growing problem. This has led to myriad harmful effects for some who are exposed to online hate. A critical first step toward stemming the tide of online hate is understanding factors associated with its creation and spread. To that end, this analysis examines factors associated with joining an ongoing attack against a targeted group online. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 60 publications
1
4
0
Order By: Relevance
“…Either way, they were the most likely to offend and be victimized repeatedly. This explanation is in line with existing research on online hate perpetration and offending (e.g., Costello & Hawdon, 2018;Hawdon et al, 2019a;Hawdon et al, 2019b). The above theories, together with subcultural and strain theories, must be further tested for their possible explanation of the victim-offender and the locale overlaps and their combinations.…”
Section: Discussionsupporting
confidence: 76%
“…Either way, they were the most likely to offend and be victimized repeatedly. This explanation is in line with existing research on online hate perpetration and offending (e.g., Costello & Hawdon, 2018;Hawdon et al, 2019a;Hawdon et al, 2019b). The above theories, together with subcultural and strain theories, must be further tested for their possible explanation of the victim-offender and the locale overlaps and their combinations.…”
Section: Discussionsupporting
confidence: 76%
“…On the individual level, personal determinants may include factors such as personality traits (Frischlich et al, 2021), attitudes and values expressed through political opinions (Costello et al, 2019), and personal experiences such as prior victimization (Wachs & Wright, 2019). Moreover, behavioral predispositions such as impulsivity (Kaakinen et al, 2020) and low self‐control (Hawdon et al, 2018) or emotional predispositions such as the ability to relate to another person's emotions (Wachs et al, 2022) were found to play a role for engaging with online hate. In the context of cyberbullying, demographics and habits of media and technology use were also considered personal determinants (Kowalski et al, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The high-choice media environment of the Internet, and particularly social media, can serve an enabling environment for radicalisation 1 as it can provide selective exposure to information (textual and visual), and reinforce existing beliefs and preferences (Hawdon et al 2019). Empirical research has shown that the resultant potential echochamber effect is likely to be stronger among more radical or conservative sub-groups, and those uninterested in (mainstream) politics and who lack exposure to diverse views from family and acquaintances (O'Hara and Stevens 2015; Dubois and Blank 2018).…”
Section: Introductionmentioning
confidence: 99%
“…While it has not been possible to determine a causal relationship between exposure to extremist online content and radicalisation (Cottee and Cunliffe 2018), frequent exposure to hate online, close identification with (and interacting with) an online community of this persuasion, are associated with greater likelihood of the individual contributing to online hate discourse (Hawdon et al 2019). Further, atrocities depicted or described in extremist online materials have been enacted or replicated by 'lone wolf' individuals.…”
Section: Introductionmentioning
confidence: 99%